Pendampingan Senam Yoga dalam Mengatasi Nyeri Menstruasi (Dysmenorrhea) - Rozifa, Annisa Wigati; Awwalul Wiladatil Qodliyah; A’im Matun Nadhiroh; Rachmawati Ika Sukarsih (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstract. The purpose of this study was to provide non-pharmacological solutions for adolescent girls to manage menstrual pain (dysmenorrhea) through yoga exercises. The program was conducted at MTs Yayasan Taman Pengetahuan Kertosono using preparation, implementation, and evaluation methods. In the preparation stage, an initial survey and coordination with the school were conducted. The implementation stage included education about dysmenorrhea and yoga exercises in overcoming dysmenorrhea pain, showing videos of dysmenorrhea yoga exercises, discussions and questions and answers, mentoring for dysmenorrhea yoga exercises, evaluation, and preparation of program implementation reports. The results showed an increase in students' understanding of menstrual pain management, and students were very enthusiastic about participating in questions and answers and discussions. In conclusion, this program succeeded in increasing students' knowledge and skills in reducing menstrual pain through dysmenorrhea yoga exercises. Yoga can be proposed as an additional/extracurricular activity at MTs Yayasan Taman Pengetahuan (YTP) Kertosono to support students' reproductive health in a sustainable manner.